2020
DOI: 10.5194/bg-17-1701-2020
|View full text |Cite
|
Sign up to set email alerts
|

Biological and biogeochemical methods for estimating bioirrigation: a case study in the Oosterschelde estuary

Abstract: Abstract. Bioirrigation, the exchange of solutes between overlying water and sediment by benthic organisms, plays an important role in sediment biogeochemistry. Bioirrigation either is quantified based on tracer data or a community (bio)irrigation potential (IPc) can be derived based on biological traits. Both these techniques were applied in a seasonal study of bioirrigation in subtidal and intertidal habitats in a temperate estuary. The combination of a tracer time series with a high temporal resolution and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(35 citation statements)
references
References 70 publications
1
34
0
Order By: Relevance
“…Importantly, Toussaint et al [ 14 ] concluded, and we confirm based on our results, that measuring processes is still essential, and their link with biological traits has not been not sufficiently studied to enable reliable and purely traits-based ecological assessments and future predictions [ 56 ]. In line with the findings of De Borger et al [ 22 ] for IPc, here BIPc also showed a stronger association with burrow ventilation depths than with ventilation intensity or magnitude of fluxes. In order to achieve a firm predictive framework for the forecasting of relationships between bioturbators and sediment respiration in different environments, the present data need to be incorporated into existing biogeochemical models [ 6 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Importantly, Toussaint et al [ 14 ] concluded, and we confirm based on our results, that measuring processes is still essential, and their link with biological traits has not been not sufficiently studied to enable reliable and purely traits-based ecological assessments and future predictions [ 56 ]. In line with the findings of De Borger et al [ 22 ] for IPc, here BIPc also showed a stronger association with burrow ventilation depths than with ventilation intensity or magnitude of fluxes. In order to achieve a firm predictive framework for the forecasting of relationships between bioturbators and sediment respiration in different environments, the present data need to be incorporated into existing biogeochemical models [ 6 ].…”
Section: Discussionsupporting
confidence: 93%
“…However, compared with related well-developed bioturbation potential, which has already been assessed and mapped for various regions [ 18 , 19 , 20 ], the classification of sediments according to their bioirrigation potential is a very recent endeavour. Despite already emerging applications, for example in the assessment of the degradation of ecosystem functions in response to sediment contamination [ 21 ], its applicability should be further explored [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, although the depth of mixing in the stratigraphic record can be estimated on the basis of ichnofabric and trace fossils (Bromley and Ekdale, 1986;Droser and Bottjer, 1988;Savrda and Ozalas, 1993), it is unclear (i) whether mixing leading to age homogenization of sedimentary particles and to the loss of sedimentary fabric was also associated with efficient irrigation and (ii) whether the ichnofabric characterizing a mixed layer in the stratigraphic record developed over yearly, decadal, or longer timescales. This uncertainty differs from temporally explicit estimates of penetration of sediment by O 2 and other solute tracers, from estimates of apparent redox potential discontinuity, or from the estimates of the mixed-layer thickness based on 234 Th that can be measured in present-day environments (Andersson et al, 2006;Maire et al, 2008;Germano et al, 2011;Gerwing et al, 2018;Solan et al, 2019;Borger et al, 2020).…”
Section: Introductionmentioning
confidence: 99%